Forging community-based outreach in Singapore through i3dm (innovative, intelligent, interactive digital media) - Pan, Zheng Xiang (2010)
This research project constitutes a multidisciplinary research agenda in the realms of computational media that harnesses the synergy among computer scientists, sports pundits, geographers, community leaders and mathematical theorists in devising an i3DM platform to address complex, dynamic information sharing.